PENGARUH WORK FAMILY CONFLICT TERHADAPTURNOVERINTENTION DENGAN STRES KERJA DAN KEPUASANKERJASEBAGAI VARIABEL MEDIASI (Studi pada Karyawan Sari MulyaPutra Group Brebes) - Fauzi Br Utoyo, Zaki Udin; Lataruva, Eisha (Faculty of Economics and Business Diponegoro University, 2024)
ABSTRACT In the modern era, career opportunities in the professional world are widelyopenfor both men and women. However, many workers experience work-family conflict, whichis an imbalance between work and family roles that makes the demands of eachroleunfulfilled. Work-family conflict can cause individuals to feel pressured and exhaustedbecause they have to divide their time and energy between both roles. If not addressed, work-family conflict can increase the level of work stress and decrease job satisfactionamong employees. Ultimately, this condition can cause employees to have a desire toleavethe company, thus increasing the turnover rate and disrupting the balance of the company. This research aims to determine the ef ect of work family conflict on turnoverintention with job stress and job satisfaction as mediating variables in the Sari MulyaPutra Group Brebes. The population used in this research was all employees of theSari Mulya Putra Group Brebes with a total sample of 51 people taken using a samplingtechnique, namely saturated sampling, that is, using all members of the populationasresearch samples. Measurements in the questionnaire use a Likert scale. Thefivehypotheses in the research were tested using quantitative methods and the data analysismethod used was path analysis. Research data processing was carried out usingSPSSversion 25. The research findings indicate that work-family conflict has a positiveandsignificant ef ect on turnover intention, work family conflict has a positive and significant ef ect on job stress, job stress has a positive and significant ef ect on turnover intention, work-family conflict has a negative and significant ef ect on job satisfaction, andjobsatisfaction does not have a negative ef ect on turnover intention. However, thepathanalysis results show that job stress cannot mediate the relationship between work-familyconflict and turnover intention, and job satisfaction also cannot mediate the relationshipbetween work-family conflict and turnover intention